PENINGKATAN PENDAPATAN PETERNAK MELALUI PENGAWETAN/PENGOLAHAN TELUR - SURYANI, NI NYOMAN; SULANDRA, KETUT (Buletin Udayana Mengabdi; Vol 6 No 1 (2007): Volume 6 No.1 - April 2007, 2012)
ABSTRACT The preserving/processing eggs training and extension in Kelurahan Penatih Denpasar Timur, Kodya Denpasar, has been held on October 11th 2005. The aim of this activity is to improve the knowledge and the skill of breeders in order to increase their income. Remembered that the breeder society, especially poultry breeder, sold their eggs in a fresh condition and totally did not do preserving/processing. The methods used in this activity were the preserving/processing technique extension and practicing the way to produce it followed by its evaluation all at one. The result were the breeders knowledge about preserving/processing eggs is increasing, so does their skill and the eggs quality we received is satisfied enough.